2012
DOI: 10.2135/cropsci2011.05.0239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seeding Rate, Nitrogen Management, and Micronutrient Blend Applications on Pith Expression in Solid‐Stemmed Spring Wheat

Abstract: The wheat stem sawfly (Cephus cinctus Norton [Hymenoptera: Cephidae]) is a serious threat to wheat (Triticum aestivum L.) and other cereal grains in the northern Great Plains. Wheat cultivars with high expression of pith in the culm of the stem (stem solidity) can minimize losses associated with sawfly infestations and subsequent stem boring of the larva. Based on the widespread area now sown to solid‐stemmed wheat, our objective was to develop an integrated nutrient and planting strategy specific to solid‐ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
3
31
1
Order By: Relevance
“…A negative relationship between grain yield and stand establishment was also observed. The negative association with stand establishment does not agree with a previous finding that reports a positive association (Beres et al, 2011c) which may be more plausible given that yield potential is dependent on optimum plant stand or a high degree of tillers per plant. The result may indicate some of the treatment combinations in this study had a higher tillering capacity than what has been previously observed.…”
Section: Resultscontrasting
confidence: 99%
“…A negative relationship between grain yield and stand establishment was also observed. The negative association with stand establishment does not agree with a previous finding that reports a positive association (Beres et al, 2011c) which may be more plausible given that yield potential is dependent on optimum plant stand or a high degree of tillers per plant. The result may indicate some of the treatment combinations in this study had a higher tillering capacity than what has been previously observed.…”
Section: Resultscontrasting
confidence: 99%
“…These N responses are similar to those reported by Beres et al (2012), where grain yields of spring wheat were optimized with N rates between 60 and 90 kg N ha (1 . In contrast, extensive work in Ontario on soft red winter wheat cultivars showed N responses between 135 and 165 kg N ha…”
Section: Grain Yieldsupporting
confidence: 85%
“…Koutroubas et al (2012) mentioned that even under low N fertilization, lodging of spelt is a common problem related to weakness of stems. In spring wheat, increasing the seeding rate resulted in a decrease in stem solidness and diameter (Beres et al 2012); thus, low seeding rates could be an option to reduce sensitivity to lodging, even though in our study, such an effect was not observed and stem measurements were not recorded. Lodging decreases threshing efficiency due to harvest losses of grain and straw; it can also affect the quality of grains by excessive moisture at harvest and inconsistent maturity.…”
Section: Results and Discussion Yields And Agronomic Measurementsmentioning
confidence: 53%
“…In western Canada, using spring spelt, Ehsanzadeh (1998) obtained the highest yield using 150 grains m (2 , whereas no yield differences were observed from 250 to 450 grains m (2 ; increasing the seeding rate led to an increase of spike density and a decrease in the number of grains per spike, but had no effect on 1000-grain weight. Beres et al (2012) mentioned that increasing the seeding rate (100, 300 and 500 grains m (2 ) of spring wheat in western Canada increased yield only from 100 to 300 grains m (2 , because at the highest seeding rate, the increased spike density was balanced by a decrease in the 1000-grain weight. In Europe, Castagna et al (1996) reported that increasing the seeding rate (200Á400 grains m (2 ) of winter spelt slightly increased hulled grain yield, and the effect of seeding rate on yield components was similar to that described by Ehsanzadeh (1998).…”
mentioning
confidence: 99%